2019
DOI: 10.1177/0969141319885994
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of women underscreened for cervical cancer who received unsolicited human papillomavirus self-sampling kits

Abstract: Objectives To evaluate experiences and reactions after receiving a mailed, unsolicited human papillomavirus self-sampling kit and identify psychosocial correlates of using kits. Methods Survey participants were underscreened women aged 30–64 who were mailed human papillomavirus kits as part of a pragmatic trial at Kaiser Permanente Washington, a United States integrated health care system. Six months after the mailing, we invited kit returners and non-returners to complete a web survey that measured psychosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…In underscreened or never-screened populations, direct mail strategies have been shown to result in higher screening uptake, enabling access to people who have not engaged with the health care system in some time. 53 Sending self-testing kits to individuals' homes via direct mail can be more cost-effective than opt-in strategies, where individuals have to seek out testing themselves, although with higher overall costs. 27 In a systematic review of interventions to improve the uptake of cervical cancer screening among lower socioeconomic groups, population screening programs were, as a whole, unlikely to remove the barriers and socioeconomic inequalities that prevent many underscreened people from participating.…”
Section: Underscreened or Never-screened Populationsmentioning
confidence: 99%
“…In underscreened or never-screened populations, direct mail strategies have been shown to result in higher screening uptake, enabling access to people who have not engaged with the health care system in some time. 53 Sending self-testing kits to individuals' homes via direct mail can be more cost-effective than opt-in strategies, where individuals have to seek out testing themselves, although with higher overall costs. 27 In a systematic review of interventions to improve the uptake of cervical cancer screening among lower socioeconomic groups, population screening programs were, as a whole, unlikely to remove the barriers and socioeconomic inequalities that prevent many underscreened people from participating.…”
Section: Underscreened or Never-screened Populationsmentioning
confidence: 99%
“…Several studies and meta-analyses have found that, compared with clinician-collected samples, self-collected HPV samples showed high diagnostic accuracy [16][17][18]. Highly acceptable or even preferred among women over clinician-collected samples [19][20][21][22][23], HPV self-sampling has garnered attention for its potential to increase screening by circumventing barriers to the Pap smear, and ease of use outside of a clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Our 2014-2017 HOME trial, which was embedded in a US health care system, found that mailing HPV self-sampling kits to underscreened individuals increased screening by 9% over usual care (26% vs 17%), similar to international trials . However, most individuals remained unscreened with low follow-up of HPV-positive results and patient understanding of testing …”
Section: Introductionmentioning
confidence: 99%
“…18,19 However, most individuals remained unscreened with low follow-up of HPV-positive results and patient understanding of testing. [18][19][20][21] As US health care systems introduce primary HPV screening with possible self-sampling, they need data to inform implementation. HPV self-sampling trials 22 have not specifically evaluated kit uptake among populations that are screeningadherent or have unknown screening history (where potential overscreening is a concern).…”
mentioning
confidence: 99%